Between Tragedy and Farce: 9/11 Compensation and the Value of Life and Death. Issue 2 (11th November 2013) - Gilbert, Emily; Ponder, Corey
Abstract This paper examines how lives have been valued (or not) in the US federal compensation programs set up in the wake of 9/11. The Victim Compensation Fund (VCF), implemented within days of the attacks, provided unlimited funds to the victims. In contrast, many first responders who developed illnesses later have had access to limited support. Only in 2011 was the Zadroga Act signed into place, which extends compensation to these workers and others. This paper compares and contrasts the two programs to make two points. One, the debates around compensation lay bare the differential values that are ascribed to life, and how biopower not only fosters life but abandons some to the point of death. Two, despite the controversies around extending compensation, the Zadroga Act was eventually enacted. Our second point is thus that war is not just destructive, but can be used to reconstitute the social and political in unanticipated ways.